2023
DOI: 10.1111/jvp.13403
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and cannabidiolic acid: Preliminary in vitro evaluation of metabolism and drug–drug interactions involving canine cytochrome P‐450, UDP‐glucuronosyltransferase, and P‐glycoprotein

Abstract: Phytocannabinoid‐rich hemp extracts containing cannabidiol (CBD) and cannabidiolic acid (CBDA) are increasingly being used to treat various disorders in dogs. The objectives of this study were to obtain preliminary information regarding the in vitro metabolism of these compounds and their capacity to inhibit canine cytochrome P450 (CYP)‐mediated drug metabolism and canine P‐glycoprotein‐mediated transport. Pure CBD and CBDA, and hemp extracts enriched for CBD and for CBDA were evaluated. Substrate depletion as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This agrees with the findings reported by Garcia et al as 3/14 dogs utilized in their study developed transient ataxia during the course of treatment with 2 mg/kg twice daily dosing of CBD/CBDA-rich hemp added to an established treatment protocol of 2 or more anti-seizure medications [8]. Both of these studies note that anti-seizure medications and CBD undergo metabolism via hepatic and gastrointestinal cytochrome p450 and hepatic conjugation activities which could alter the serum concentrations of typical anti-epileptic drugs; however, in the Garcia study, no serum alterations of phenobarbital or zonisamide were observed [8,9,21]. In a later study by Donovan et al, the interactions of CBD and phenobarbital were elegantly examined showing no influence of CBD on phenobarbital serum concentrations in normal healthy beagles at similar or higher dosing [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with the findings reported by Garcia et al as 3/14 dogs utilized in their study developed transient ataxia during the course of treatment with 2 mg/kg twice daily dosing of CBD/CBDA-rich hemp added to an established treatment protocol of 2 or more anti-seizure medications [8]. Both of these studies note that anti-seizure medications and CBD undergo metabolism via hepatic and gastrointestinal cytochrome p450 and hepatic conjugation activities which could alter the serum concentrations of typical anti-epileptic drugs; however, in the Garcia study, no serum alterations of phenobarbital or zonisamide were observed [8,9,21]. In a later study by Donovan et al, the interactions of CBD and phenobarbital were elegantly examined showing no influence of CBD on phenobarbital serum concentrations in normal healthy beagles at similar or higher dosing [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not see any notable alterations in CBC parameters that were related to a treatment effect; however, CBCs were not performed at each stage of the study. Repeated CBCs at each phase were not performed due to prior studies showing no alterations in any CBC parameters using doses between 5 and 10 mg/kg per day in studies examining mixed cannabinoids or CBD-rich hemp products, to date [11,21]. All of the changes over time surrounded primarily red blood cell alterations and reticulocytosis which could be related to environment change as feral dogs and treatment of GI parasitism.…”
Section: Discussionmentioning
confidence: 99%